Effects on training and detraining on physical function, control of diabetes and anthropometrics in type 2 diabetes; a randomized controlled trial. (February 2015) - Park, Sang-Young; Lee, In-Hee
Abstract The purpose of this study was to investigate the effect of circuit exercise training and detraining, which is defined by termination of training without additional physical activities, in type 2 diabetic patients. Elderly with type 2 diabetes were divided into a group that exercised for 1 h three times a week for 12 weeks, followed by detraining for 8 weeks, or into a control group. Muscular strength, endurance, flexibility, agility, balance, body mass index (BMI), glycosylated hemoglobin (HbA1c), and blood lipid profile were measured. Of the 98 diabetic participants who joined this study, 37 patients completed the program (exercise group = 24, control group = 13). After training, muscular strength, flexibility, balance, agility, and endurance in the training group were significantly higher than at baseline and compared to the control group. HbA1c levels decreased in the training group. There was no significant improvement in BMI and blood lipid profile in either group. Flexibility and agility in the training group declined significantly after detraining. In spite of this decline, flexibility and agility were significantly higher compared to the baseline and to the control group. In type 2 diabetic patients, circuit training had a beneficial effect on the indices of physical function and glucose metabolism. Training resulted in good improvement; and during detraining, the effect of exercise training was maintained except in some parameters.